Osborn Awards for the best recordings of African music for the year 1953 - Tracey, Hugh (International Library of African Music, 1954)
The African Music Society has pleasure in announcing the Osborn Awards for 1953. 275 entries were received from all over Africa for the consideration of the Judges, and eleven Awards of Seven Guineas each were recommended and nine Highly Commended of Two Guineas each.
Keywords: Ethnomusicology; Awards; African Music